Powerful Antibacterial Peptides from Egg Albumin Hydrolysates - Abdul-Raouf Al-Mohammadi; Ali Osman; Gamal Enan; Seham Abdel-Shafi; Mona El-Nemer; Mahmoud Sitohy; Mohamed A. Taha (Antibiotics, 2020)
Native egg albumin (NEA) was isolated from hen eggs and hydrolyzed by pepsin to produce hydrolyzed egg albumin (HEA). HEA was chemically characterized and screened for its antibacterial activity against 10 pathogenic bacteria (6 Gram (+) and 4 Gram (−)). The SDS-PAGE pattern of NEA showed molecular weights of hen egg albumin subunits ranging from 30 to 180 kDa. The highest intensive bands appeared at a molecular mass of about 50 and 97 kDa. Ultra-performance liquid chromatography (UPLC) of the peptic HEA revealed 44 peptides, 17 of them were dipeptides, and the other 27 fractions corresponded to bigger peptides (3–9 amino acids). The dipeptides and big peptides represented 26% and 74% of the total hydrolysate, respectively. The MIC of HEA was about 100 μg/L for Listeria monocytogenes, Bacillus cereus, Staphylococcus aureus, Salmonella typhimurium, Streptococcus pyogenes, and Klebsiella oxytoca and 150 μg/L for Pseudomonas aeruginosa, Bacillus subtilis, and Listeria ivanovii and 200 μg/L for Escherichia coli. L. monocytogenes was the most sensitive organism to HEA. Mixtures of HEA with antibiotics showed more significant antibacterial activity than individually using them. Transmission electron microscopy (TEM) revealed various signs of cellular deformation in the protein-treated bacteria. HEA may electrostatically and hydrophobically interact with the cell wall and cell membrane of the susceptible bacteria, engendering large pores and pore channels leading to cell wall and cell membrane disintegration. Higher cell permeability may, thus, occur, leading to cell emptiness, lysis, and finally death. Alternatively, no toxicity signs appeared when HEA was administrated to Wistar Albino rats as one single dose (2000, 5000 mg/kg body weight) or repeated daily dose (500 and 2500 mg/kg body weight/day) for 28 days to disclose the possible toxicity hazards. HEA did not produce any death.